Analysis of Determinants of Sharia Stock Price Index in the Jakarta Islamic Index (JII) for the Year 2015–2025 - Sarah Fitria Harahap; Maryam Batubara; Yusrizal (LP2M IAIN Palopo, 2026)
The purpose of this research is to determine the impact of inflation, exchange rates, and world oil prices on the Islamic stock price index in the Jakarta Islamic Index (JII) from 2015 to 2025. The research method used is a quantitative method with a multiple linear regression model, and the data source is secondary data obtained from the official websites of BPS and IDX. The data analysis techniques used are classical assumption tests, multiple linear regression tests, and hypothesis tests. Based on the data analysis results, inflation has a positive and insignificant effect on the JII. The exchange rate has a negative and significant effect on the JII, and world oil prices have a positive and insignificant effect on the JII. Simultaneously, inflation, the exchange rate, and world oil prices influence the JII by 66.2%, while the remaining 33.8% is explained by other variables outside the model. The results of this study imply that investors should pay more attention to exchange rate developments when considering investment decisions in sharia stocks. For the government and relevant authorities, exchange rate stability is one of the factors that need to be considered in maintaining the stability of the sharia capital market.